2018
DOI: 10.1186/s12875-018-0800-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of standardized nursing care plans to achieve A1C, blood pressure, and LDL-C goals among people with poorly controlled type 2 diabetes mellitus at baseline: four-year follow-up study

Abstract: BackgroundNo studies that have measured the role of nursing care plans in patients with poorly controlled type 2 diabetes mellitus. Our objectives were firstly, to evaluate the effectiveness of implementing Standardized languages in Nursing Care Plans (SNCP) for improving A1C, blood pressure and low density lipoprotein cholesterol (ABC goals) in patients with poorly controlled type 2 diabetes mellitus at baseline (A1C ≥7%, blood pressure ≥ 130/80 mmHg, and low-density lipoprotein cholesterol≥100 mg/dl) compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…The literature supported the adoption of an SNL and the use of technology to support care planning. 4,13,16,33 Fortuitously, health information technology has become ubiquitous, and nursing documentation moved into the EHR. According to the Office of the National Coordinator for Health Information Technology, 96% of all nonfederal hospitals have an EHR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature supported the adoption of an SNL and the use of technology to support care planning. 4,13,16,33 Fortuitously, health information technology has become ubiquitous, and nursing documentation moved into the EHR. According to the Office of the National Coordinator for Health Information Technology, 96% of all nonfederal hospitals have an EHR.…”
Section: Discussionmentioning
confidence: 99%
“…12 Another research team reported diabetic patient outcomes more likely to reach hemoglobin A1C, blood pressure, and low-density lipoprotein cholesterol goals when electronic standardized nursing care plans were used (OR = 0.97; 95% confidence interval, 0.79-1.19; P = .76). 13 An observational study exploring Author Affiliation: Frederick Health Hospital, Frederick, MD.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, standardized languages are required by the clinical information system to assist clinicians with nursing practice documentation (Sani & Sani, 2017). The research-based tool that is currently utilized in adult care settings in developed countries like the United States and Sweden, among others, has helped in labeling and identifying the contribu-tions of nursing to healthcare delivery systems, as well as served as clinical protocol in these settings (Cárdenas-Valladolid et al, 2018). This research-based clinical protocol is known as the SNCPs.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent systematic review, nursing classification systems and standardized nursing languages are crucial for the successful integration of nursing documentation into the electronic record (Johnson, Edward, & Giandinoto, ). Using the nursing process and the NANDA‐I, NIC, and NOC standardized nursing languages in the electronic patient record makes it possible to increase the visibility of nursing practice and to assess the degree of influence of nursing on the health outcomes sensitive to this practice (Cárdenas‐Valladolid et al., ; Flanagan, ), both on single discipline's outcomes, more specific outcomes, as well as on multidisciplinary, more comprehensive outcomes (Duffy, ; Moorhead, Johnson, Mass, & Swanson, ; Pérez‐Rivas et al., ).…”
mentioning
confidence: 99%